Makna “Korongtigi” dalam Prosesi Pernikahan Adat Mangkasara’ di Bontoala Kabupaten Gowa - Rismayanti, Rismayanti; Dahlan, Mubarak (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2024)
This research aims to find out: korongtigi procession in Mangkasara' traditional marriage in Bontoala Village, Gowa Regency, the meaning of korongtigi, and the lost tradition in korongtigi procession in Mangkasara Traditional Marriage. This research uses descriptive qualitative research with data collection through observation, documentation, interviews. The results showed that: (1) korongtigi procession in Mangkasara' Traditional Wedding is still a sacred procession carried out before the traditional wedding. (2) korongtigi has a deep meaning for the bride and groom which contains blessings from the family in each procession so that the marriage becomes sakinah mawaddah and warahmah. (3) There is nothing missing in the korongtigi procession, the process is still the same as the previous korongtigi procession, which begins with a'bu'bu to purify themselves before starting the korongtigi procession.